Occurrence Regularity of Myzus persicae and Aphid- transmitted Virus Disease in Zhenyuan County of Guizhou - Jing, Yang; Jie, Chen; Rusong, Yang; Jun, Tang; Guangjin, Zou; Yan, Yang (Plant Diseases and Pests(植物病虫害研究：英文版), 2016)
[ Objective] The paper provided a reference for establishment of effective prevention mechanism against aphids in Zhenyuan tobacco area. [ Melllod ] The initial population quantity of aphids in early spring, migration of winged aphids, occurrence regularity and damage status of Myzus persicae and aphid-transmit- ted virus （PVY ＋ CMV） were investigated in Zhenyuan County from 2014 to 2015 using 10-point checkerboard sampling method, yellow dish trapping method and 5-point sampling method. [ Result] The total amount of aphids in Brassica campestris was the largest among overwintering hosts, with an average of 18.44 speci- men/plant. The migration of winged aphids presented bimedal pattern; the population dynamics of wingless aphids presented unimodal pattern, and the occurrence peak was from May to June. [ Conclusion] Field control against M. persicae in tobacco fields should be conducted from mid May to early June.